You belong to me - Clark, Mary Higgins (Pocket Books fiction, 2012)
A beautiful and dedicated young psychoanalyst is terrified to discover that her beloved sister is determined to marry one of the doctor's former patients, a man who conceals a dangerously jealous, obsessive nature, as well as a pattern of abuse, behind his charming and wealthy facade.